2021
DOI: 10.1021/acschemneuro.1c00098
|View full text |Cite
|
Sign up to set email alerts
|

C1 Inhibits Liquid–Liquid Phase Separation and Oligomerization of Tau and Protects Neuroblastoma Cells against Toxic Tau Oligomers

Abstract: The pathological aggregation of tau is one of the major contributing factors for several neurodegenerative tauopathies, including Alzheimer's disease. Here, we report that C1, a synthetic derivative of curcumin, strongly inhibited both the aggregation and filament formation of purified tau and protected neuroblastoma cells from the deleterious effects of the tau oligomers. Using confocal microscopy, C1 was found to reduce both the size and number of the tau droplets and increased the critical concentration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 58 publications
0
33
0
Order By: Relevance
“…As other factors that modulate α-Syn aggregations have the possibilities to regulate LLPS as well, the phase transition of α-Syn could be a general key target for PD treatment. In support of this, recent studies have reported that protein LLPS can be modulated by small molecules, either inducing or preventing the formation of liquid droplets ( 77 , 78 ).…”
Section: Discussionmentioning
confidence: 78%
“…As other factors that modulate α-Syn aggregations have the possibilities to regulate LLPS as well, the phase transition of α-Syn could be a general key target for PD treatment. In support of this, recent studies have reported that protein LLPS can be modulated by small molecules, either inducing or preventing the formation of liquid droplets ( 77 , 78 ).…”
Section: Discussionmentioning
confidence: 78%
“…Thioflavin S binds to amyloids, and the fluorescence intensity of Thioflavin S increases upon binding to amyloids. Therefore, the increase in the fluorescence intensity of Thioflavin S is widely used to determine tau aggregation. Tau is a highly soluble unstructured protein and it forms oligomers and filaments in vitro when incubated in the presence of either heparin, RNA, or arachidonic acid. In this work, we monitored the effects of several trivalent metal ions (Fe 3+ , Cr 3+ , Al 3+ , La 3+ , and V 3+ ) on the aggregation of tau in the absence and presence of heparin using Thioflavin S fluorescence (Figure A–G). Thioflavin S displayed weak fluorescence when incubated with tau without heparin (Figure A,F).…”
Section: Resultsmentioning
confidence: 99%
“…Tau (8 μM) in 25 mM PIPES buffer pH 7.4 was incubated without or with 10 μM Fe 2+ /Fe 3+ for 10 min and further, incubated with 8 μM heparin for 6 h at 37 °C in shaking conditions. Then, 1 mL from each sample was analyzed in the DLS instrument (Zetasizer, Malvern) as described earlier . The samples were also analyzed for atomic force microscopy as reported previously. , Briefly, the samples were adsorbed onto a freshly cleaved mica disc and tau aggregates was observed using the Asylum MFP-3D Bio-AFM.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that BCOV could reduce the serum LDL level significantly in obese rats [ 140 ]. Curcumin is both an antioxidant and an antidiabetic agent [ 141 ]; it had been reported that curcumin inhibited the oligomerize of tau [ 142 ]. This vanadium compound is deserved to be investigated in further studies in order to determine the therapeutic effects of vanadium compounds on AD.…”
Section: Discussionmentioning
confidence: 99%